THE EFFECTIVENESS OF USING DIGITAL STORYTELLING IN TEACHING SPEAKING AT SMA MUHAMMADIYAH 9 MAKASSAR - Harmawati; Nunung Anugrawati; Eka Prabawati Rum (FKIP Unismuh Makassar, 2022)
The objective of the research was to find out whether or not the used of digital storytelling can improve students’ speaking fluency at SMA Muhammadiyah 9 Makassar. The researcher used a purposive sampling method and took only class XII the sample of the research which consisted of 37 students. In addition the researcher applied an instrument of the research namely oral test. In pre-test and post-tes the researcher gave topics through digital storytelling to stimulate the students to speak in front of the class. In pre-test and pos-test the students one by one to speak face to face with the researcher in the class.Based on the result of the data analysis it was found that the mean score of pre-test was 3.45 and the mean score of post-test 4.54. by applying the level of significance 0.05 with the degreeof fredom (df) = 37 - 1 = 36, it was found that the result of t-test was 10.33 which was greater that t-table value 1.688. It mean that the alternative hypothesis was accepted and Null hypothesis was rejected. It could be conducted that digital storytelling materials was significant effect toward students speaking fluency through asking and answer question.